Corneal Graft Rejection after Yellow Fever Vaccine: A Case Report. (4th July 2022) - Vignapiano, Roberto; Vicchio, Lidia; Favuzza, Eleonora; Cennamo, Michela; Mencucci, Rita
ABSTRACT: Purpose: To report an unusual case of corneal graft rejection after yellow fever vaccine. Methods: Case report. Results: We have described the case of a 48-year-old man who developed a corneal graft rejection in the left eye 3 weeks after a yellow fever vaccination. The ophthalmic examination of the left eye revealed conjunctival hyperemia, corneal graft edema with Descemet folds, and fine keratic precipitates. No abnormalities were found in the right eye. The episode of graft rejection fully recovered after a short course of systemic and topical steroid treatment. Conclusions: This is the first case report of corneal transplant rejection temporally associated with yellow fever vaccination. Although the yellow fever vaccine is a very safe and efficacious vaccine, the occurrence of vaccine-related rejection may be more frequent than reported. Both patients and ophthalmologists should be aware of possible vaccine-related complications which may be potentially sight-threatening.